Berger disease: therapeutic algorithm proposal and chronic renal failure predictive factors. - Pessegueiro, Pedro (2003)
Berger disease is described as a glomerulonephritis by anti-IgA and anti-IgG immune complexes and it has become the most common form of glomerulonephritis, affecting up to 1,3% of the population, most often affecting young adult males. Berger disease etiopathogenesis is still unknown, being well recognized its temporal associations with bacterial and viral infections, as well with genetic factors which lead some authors to suggest the existence of a founder effect. Characteristically IgA nephropathy presents intermittent macroscopic hematuria following mucosal infections, nonnephrotic proteinuria and persistent microscopic hematuria. A renal biopsy should be performed in patients in whom this diagnosis is suspected, particularly if there is persistent proteinuria. IgA nephropathy was initially considered a benign disease, but long term follow up studies have shown the course to be slowly progressive with up to 50% of the patients developing terminal renal failure. The authors propose themselves a therapeutic algoritm, as well as clinical indicators of evolutive course.